The influence of stimulus proximity on judgments of spatial relationships in patients with chronic unilateral right or left hemisphere stroke - Williamson, John B.; Haque, Salsabil; Burtis, Brandon; Harciarek, Michal; Lamb, Damon; Zilli, Eduardo; Heilman, Kenneth M. (Journal of clinical and experimental neuropsychology, 2014)
Objective: This was to learn how chronic right hemispheric damage (RHD) versus left hemispheric damage (LHD) may influence attentional biases in proximal and distal space. Background: Prior research has suggested that the left hemisphere primarily attends to proximal space and the right hemisphere to distal space. The purpose of this study was to contrast line bisection performed in proximal versus distal space in patients with chronic LHD versus RHD. Design/method: Participants were 32 LHD and 26 RHD patients who sustained a stroke a mean of 3.4 years prior to testing, along with 9 healthy controls. Subjects attempted to bisect 30 lines in proximal space and 30 lines in distal space. Results: Patients with both RHD and LHD had a greater contralesional bias in proximal than distal space (rightward bias for patients with LHD and leftward bias for patients with RHD). Compared to controls, patients with LHD were most different in proximal space, and patients with RHD were most different in distal space. Conclusions: Proximity appears to influence spatial judgments of patients with RHD and LHD in an opposing manner. Relatively, both patient groups bisect lines contralesionally in proximal space and ipsilesionally (relative to proximal) in distal space. Patients with RHD have the biggest difference between their proximal and distal judgments. The reason for these differences is unknown. However, these biases may be related to an attentional or action-intentional grasp or a learned compensation strategy, and proximity may increase the allocation of attention or intention and thereby enhance this grasp or use of this compensation strategy. Another contributing factor may be dominance of the left and right hemisphere for information presented in proximal and distal space, respectively.